2008
DOI: 10.1021/jp802959c
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Oxidation of Nitrogen Dioxide with TiO2 Thin Films under Continuous UV-Light Illumination

Abstract: A deactivating behavior of TiO2 photocatalysts in NO2 oxidation to HNO3 was studied with use of TiO2 nanoparticulate thin films (0.5−1.5 μm thick) under UV light illumination over 10 h. The photocatalytic activity was decreased with accumulation of HNO3 on the TiO2 surface. For thicker TiO2 films, the deactivation rate was found to be slower. The amount of HNO3 trapped on the TiO2 surface was increased and finally saturated, at which the largest amount of HNO3 was proportional to the thickness of the film. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 14 publications
5
69
1
1
Order By: Relevance
“…A deactivating behaviour of TiO 2 in the reaction with NO 2 under UV irradiation observed in the present study supports the previous observations of Ohko et al (2008). These authors have observed that the photocatalytic activity was decreased with accumulation of HNO 3 on the TiO 2 surface and concluded that the produced HNO 3 inhibited the photocatalytic heterogeneous reaction as a physical barrier.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A deactivating behaviour of TiO 2 in the reaction with NO 2 under UV irradiation observed in the present study supports the previous observations of Ohko et al (2008). These authors have observed that the photocatalytic activity was decreased with accumulation of HNO 3 on the TiO 2 surface and concluded that the produced HNO 3 inhibited the photocatalytic heterogeneous reaction as a physical barrier.…”
Section: Discussionsupporting
confidence: 92%
“…In several previous studies (e.g. Lin et al, 2006;Ohko et al, 2008) it was observed that the photocatalytic activity of the TiO 2 film can be fully regenerated after rinsing with water. In the present work, we have observed similar behaviour: the deactivated TiO 2 sample was regenerated after being immersed in water.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…75 A maximum density of B2 molecules of HNO 3 nm À2 TiO 2 was reported. 74 With the maximum amount of oxidized NO found during this work (n rem = 9.25 Â 10 À6 mol) and the geometric surface area of the sample a maximum density of B1 molecule of HNO 3 per 1000 nm 2 is calculated to be produced during a single experimental run performed in this work indicating that the TiO 2 surface is far from being saturated by adsorbed HNO 3 . It is therefore suggested that a dynamic equilibrium between NO, HNO 2 /NO 2 À , and NO 2 is established comprising surface reactions as well as adsorption-desorption equilibria, but that the final oxidation product is continuously accumulated on the photocatalyst surface during the entire experimental run, thus blocking the NO adsorption sites.…”
Section: Discussionmentioning
confidence: 65%
“…The respective photocatalytic oxidation pathway of NO, where water and all nitrogen compounds present at the photocatalyst surface are in equilibrium with the gas phase, is outlined in Table 2. [62][63][64] Profound objections have been raised against this pathway by Ohko and co-workers, 24,25,74 who claimed the contribution of a terminal (bridging) oxygen species, TiO 2 (O s ), and oxygen vacancies, TiO 2 (&), at the TiO 2 surface to the photocatalytic NO oxidation. The NO reaction pathway suggested by this group is presented in Table 3.…”
Section: Discussionmentioning
confidence: 99%